2006
DOI: 10.1007/s00405-006-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster laryngitis: case report and serological profile

Abstract: Compared to herpes zoster oticus, varicella zoster virus (VZV) reactivations in immunocompetent patients are rare in laryngeal region. Usually, associated vocal cord paralyses are reported. Herein is a case report of a patient with laryngeal zoster without any associated motor disorders. An attempt is made to assign the distribution of mucosal eruptions to the appropriate neuroanatomical structures. A description of the serological course of VZV IgM and IgG are provided. Vesicles were found on the left sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…In our patient, whose diagnosis was confirmed serologically, biopsies showed no evidence of those features. It is important to note that serological IgM determination, although reliable, is not useful for immediate decision-making as the antibodies appear only 8-10 days after the eruption [1,5,6]. Fortunately, the serological findings of our patient were available 8 days after admission, enabling prompt diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our patient, whose diagnosis was confirmed serologically, biopsies showed no evidence of those features. It is important to note that serological IgM determination, although reliable, is not useful for immediate decision-making as the antibodies appear only 8-10 days after the eruption [1,5,6]. Fortunately, the serological findings of our patient were available 8 days after admission, enabling prompt diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Upper gastrointestinal endoscopy revealed mucosal lesions, and polymerase chain reaction (PCR) of erosional exudates confirmed the clinical diagnosis; antiviral therapy and corticosteroids led to complete healing [4]. Yet another patient, who had vesicles on unilateral distribution areas of the superior laryngeal nerve and was diagnosed with laryngeal zoster on the basis of serology, showed no evidence of motor disorders [5]. In a study of five patients with idiopathic associated laryngeal paralysis, all with significant changes in serum VZV antibody levels, the outcome was poor in the two cases in which antiviral therapy was delayed [6].…”
Section: Discussionmentioning
confidence: 90%
“…Herpes zoster infection of the larynx accompanied by RHS with cranial polyneuropathy is extremely rare, with only few reported cases in the literature. 1,[6][7][8][9] About 12% of all peripheral facial nerve palsies are caused by varicella zoster virus. The occurrence rate of associated cranial polyneuropathy has been reported to be 1.8-3.2% and cranial nerves VII, VIII, IX and X are the ones most commonly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes zoster laryngitis is a rare inflammatory disease and is usually indicated by presenting symptoms that manifest as laryngeal mucosal eruptions with or without vocal cord palsy. 4,7,8 In this review, we excluded reported cases without laryngeal mucosal lesions in the medical literature, even if patients with RHS had vagus nerve palsy. A review of the medical literature disclosed 4 reported cases of herpes zoster laryngitis accompanied by RHS ( Table 1).…”
Section: Discussionmentioning
confidence: 99%